Rancang Bangun Sistem Informasi Akuntansi Dengan Metode Waterfall Untuk Memudahkan Laporan Pada Koperasi Warung Kita Pamijahan Bogor - Perdana, Jamal Andrian; Anjaswani, Muhammad; Prasetyo, Arfhan; Solecha, Kusmayanti (JAIS - Journal of Accounting Information System, 2022)
In today's era of globalization, information technology is advancing rapidly. As for computers, which are equipment created to facilitate human work, when achieving progress both in the manufacture of hardware and software. Warung Kita Cooperative really needs an information system that supports and provides satisfactory service to customers. For this reason, the author tries to make a Final Project regarding the system of selling goods at the Warung Kita Pamijahan Bogor Cooperative which has not yet been computerized. At the time the Warung Kita Cooperative was engaged in the sale of goods. The existing system at the Warung Kita Cooperative is still done manually, starting from recording goods, making sales notes, to storing other data related to the sales process to making reports, making it possible during the process an error occurred in the recording, less the accuracy of the reports made and the delay in finding the required data. The design of this information system is the best solution to solve the problems that exist in this company, and with a computerized system, an effective and efficient activity can be achieved in supporting activities in this company. The computerized system is better than the manual system to run more effectively and efficiently and the current sales system is more conducive than the previous system